The role of post-translational modifications in driving abnormal cardiovascular complications at high altitude - Hou, Jun; Wen, Xudong; Long, Pan; Xiong, Shiqiang; Liu, Hanxiong; Cai, Lin; Deng, Haoyu; Zhang, Zhen (Frontiers in Cardiovascular Medicine, 2022)
The high-altitude environment is characterized by hypobaric hypoxia, low temperatures, low humidity, and high radiation, which is a natural challenge for lowland residents entering. Previous studies have confirmed the acute and chronic effects of high altitude on the cardiovascular systems of lowlanders. Abnormal cardiovascular complications, including pulmonary edema, cardiac hypertrophy and pulmonary arterial hypertension were commonly explored. Effective evaluation of cardiovascular adaptive response in high altitude can provide a basis for early warning, prevention, diagnosis, and treatment of altitude diseases. At present, post-translational modifications (PTMs) of proteins are a key step to regulate their biological functions and dynamic interactions with other molecules. This process is regulated by countless enzymes called “writer, reader, and eraser,” and the performance is precisely controlled. Mutations and abnormal expression of these enzymes or their substrates have been implicated in the pathogenesis of cardiovascular diseases associated with high altitude. Although PTMs play an important regulatory role in key processes such as oxidative stress, apoptosis, proliferation, and hypoxia response, little attention has been paid to abnormal cardiovascular response at high altitude. Here, we reviewed the roles of PTMs in driving abnormal cardiovascular complications at high altitude.